Evaluasi Penerapan Standar Sanitasi dan Pengelolaan Sampah pada Desain Pasar Rakyat di Kawasan Lahan Basah - Alkausar Alkausar; Najatiatul Mufidah; Aulia Rahmah (JAUR (JOURNAL OF ARCHITECTURE AND URBANISM RESEARCH), 2026)
Public markets located in wetland areas face particular challenges in utility planning, especially regarding sanitation and waste management, due to low topography, saturated drainage, and high waterlogging potential. This study aims to evaluate the implementation of sanitation and waste management standards in public market designs situated in wetland environments. The research employed a qualitative-descriptive approach with a comparative case study of two student architectural works. Data were collected from design documents, working drawings, and 3D models, and analyzed using a weighted scoring evaluation instrument based on four parameters: wastewater drainage systems, public toilet availability, waste management systems, and utility adaptation to wetland characteristics. The results show that Design A achieved 68% compliance with standards, excelling in waste management and circulation efficiency, but less adaptive to inundation conditions. Meanwhile, Design B reached 80% compliance, performing better in closed drainage systems, sanitation facilities, and site elevation adaptation. The adaptivity analysis indicates that both designs complement each other to form a sustainable public market concept suited to wetland ecological characteristics. This study highlights the importance of integrating vernacular architecture with green utility systems, while also opening opportunities for green and digital architecture applications in developing adaptive and sustainable market designs for wetland environments.